Instagram's Perloction, "Rizky Billar will Report these 3 Persons, Considered Shalam in the Middle of KDRT Cases - Tiara Sari; Yusni Khairul Amri (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2023)
Cases of domestic violence that have occurred lately have always claimed victims from the women's side, this is due to the patriarchal culture that considers women as inferior and subordinated. This domestic violence case data uses primary data from Instagram comments on the @medantalk account as many as 17 comments. Speech act theory is a sub-field of pragmatics. This field of study is concerned with the ways in which words can be used not only to present information but also to carry out actions. This theory considers three levels or components of speech: locutionary acts (making a meaningful statement, saying something the listener understands), illocutionary acts (saying something with a purpose, such as to inform), and perlocutionary acts (saying something to cause someone to act). Based on these data, the speech act theory analysis tool proposed by John L. Austin (1962) was used. This theory describes 2 types of utterances, namely constative and performative utterances. The forms of domestic violence found were physical, psychological, and physical violence. From these problems victims of domestic violence experience a long process of trauma or psychological recovery and become survivors of domestic violence. Based on the commentary data after being analyzed using Austin's speech act theory, the results of the analysis were found to be two types of responses, both positive and negative, with the meaning of perlocutionary acts varied greatly. Positive responses are in the form of (1) appreciation, (2) support and (3) expectations of government policies and activities, while negative responses contain (1) disappointment, (2) anger, (3) annoyance, (4) questions of lack of trust in government policy in dealing with domestic violence in Indonesia.